Fuzzy Linear Programming Solved via Solving Linear Programming - REDDY, DR.RAJESHWARA (The journal of contemporary issues in business and government, 2019)
Engineering design is typically plagued with inaccuracies due to the complexity of many real-world engineering systems. Fuzzy linear programming issues play an important part in fuzzy modelling, which is able to express uncertainty in the real world. Dubois and Prade's LR fuzzy number is one of the most practical themes in recent research, with several useful and simple approximation arithmetic operators on it. Fuzzy vectors occur as a vector of triangular fuzzy integers in various vector calculations. To begin, we are looking for a nonnegative fuzzy vector x in this situation fuzzy numbers. Here, our main scope is finding some nonnegative fuzzy vector ~x in which maximizes the objective function ~ ~ z = c x so that ~ ~ A x = b , where A and ~b are a real matrix and a fuzzy vector respectively, and n c 1× is a real vector too.